Prognostic Factors in De Novo Metastatic Renal Cell Carcinoma: A Report From the Latin American Renal Cancer Group. (2021) - Abreu, Diego; Carvalhal, Gustavo; Gueglio, Guillermo; Tobia, Ignacio; Garcia, Patricio; Zuñiga, Alvaro; Meza, Luis; Bengió, Rubén; Scorticati, Carlos; Castillejos, Ricardo; Rodriguez, Francisco; Autran, Ana María; et al.
Abstract : PURPOSE: To assess the effect of clinical and pathological variables on cancer-specific and overall survival (OS) in de novo metastatic patients from a collaborative of primarily Latin American countries. PATIENTS AND METHODS: Of 4, 060 patients with renal cell carcinoma diagnosed between 1990 and 2015, a total of 530 (14.5%) had metastasis at clinical presentation. Relationships between clinical and pathological parameters and treatment-related outcomes were analyzed by Cox regression and the log-rank method. RESULTS: Of 530 patients, 184 (90.6%) had died of renal cell carcinoma. The median OS of the entire cohort was 24 months. American Society of Anesthesiology classification 3-4 (hazard ratio [HR]: 1.64), perirenal fat invasion (HR: 2.02), and ≥ 2 metastatic organ sites (HR: 2.19) were independent prognostic factors for 5-year OS in multivariable analyses. We created a risk group stratification with these variables: no adverse risk factors (favorable group), median OS not reached; one adverse factor (intermediate group), median OS 33 months (HR: 2.04); and two or three adverse factors (poor risk group), median OS 14 months (HR: 3.58). CONCLUSION: Our study defines novel prognostic factors that are relevant to a Latin American cohort. With external validation, these easily discerned clinical variables can be used to offer prognostic information across low- and middle-income countries.